POPULATION DYNAMICS AND GEOCHEMISTRY OF BENTHIC AND PLANKTONIC FORAMINIFERA TO INTERPRET THE PALEOCEANOGRAPHIC CHANGES ACROSS THE CENOMANIAN-TURONIAN OCEANIC ANOXIC EVENT 2 AT LOW AND HIGH LATITUDES - AMAGLIO, GIULIA (Università degli Studi di Milano, 2025)
This PhD research project has investigated benthic and planktonic foraminiferal dynamics across one of the greatest environmental perturbations that occurred throughout the Earth’s history, namely the Cenomanian-Turonian Oceanic Anoxic Event 2 (OAE 2). It is globally marked by a positive δ13C excursion due to the deposition and burial of large amounts of organic matter in the ocean. The exact causes of OAE 2 are still studied but it is understood that it might be due to a combination of different factors including the emplacement of the Large Igneous Provinces (LIPs), fluctuations of the sea-level, changes in ocean circulation. For this study, four stratigraphic sections have been selected to document how global changes impacted at low and high latitudes. The stratigraphic sections are Clot Chevalier in the Vocontian Basin (SE France) and Eastbourne in the Anglo-Paris Basin (SE England) at low latitudes and IODP Sites U1513 and U1516 in the Mentelle Basin (SW Australia) at high latitudes. Taxonomy, quantitative and statistical analysis have been performed on foraminifera to reconstruct paleoenvironmental and paleoceanographic changes across the OAE 2. In addition, boron isotopes analysis on foraminiferal tests of DSDP Site 463 and of IODP Sites U1513 and U1516 have been conducted to obtain information about ocean acidification across the OAE 2. Samples at low and high latitudes show a continuous foraminiferal record across the OAE 2 displaying high adaptability to extreme environmental conditions, except for a distinct low carbonate interval at Sites U1513 and U1516 characterized by the absence of calcareous taxa. Foraminiferal abundance patterns exhibit notable variances between low and high latitudes with relatively low species diversity and dominance of opportunistic taxa at Sites U1513 and U1516 and with moderate abundances and high species diversity at Clot Chevalier and Eastbourne. This study has delineated six intervals across the Cenomanian-Turonian boundary interval, each marked by unique foraminiferal ...